Tubular Biogas digester berbahan Buis Beton: Desain Konseptual, Potensi dan Analisa Ekonomi - Anatta Wahyu Budiman; Muhammad Cahyadi; Ahmad Pramono; Muchammad Yusuf Firdaus; Yazid Rizal Azinuddin; Riki Agung Prasetya; Sofian Pradipta Respati Saputra (CHEMICA: Jurnal Teknik Kimia, 2017)
Biogas is becoming a main potential renewable energy resource that provides an environmentally friendly energy easily accessed by people in the rural area. So far, there are three main common concepts of biogas digester as the Fixed Dome biogas digester, the floating dome digester, and the Baloon Plastic digester. With their specific characteristics, the fixed dome and the balloon plastic digester are potential to be applied in Indonesia. In this work, the modification of fixed dome biogas digester concept using cylindrical concrete (buis beton) is introduced. This novel technology promises comparable strength and leaks free characteristics of fixed dome concept, with several benefits such as easier construction and more economical. A conceptual design toward economical aspects is presented in this manuscript.